PENERAPAN ANALISIS SWOT DALAM PERUMUSAN STRATEGI BERSAING PADA EDDY JAYA PHOTO - Rahayu, Dewi Tri; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out and to conduct the SWOT analysis as the fundamental of the strategypreparation in order to create the competitive advantage in Eddy Jaya Photo. The research is conducted by usingqualitative methods which consists of internal and external factors identification. Internal factors consist of goodreputation, product and service quality, experienced and professional employees, customer trust, incentive givento the employees, the inappropriate facilities, the promotion strategy which is not widely yet, the lack of HR, thecompany location, and the service of video editing is from the outside of the company. External factors consistof complete offering product, PAPVOS organization, good corporation with organized event, there are new andyoung photographers, the competition among competitors, the changes of customer taste, and credibility. Theresult of this research shows that the company uses the SO strategy and differentiation strategy as the competestrategy. Based on the result of the research it can be concluded that by conducting the SWOT, the process ofstrategy preparation it can create the competitive advantage from the company.Keywords: SWOT Analysis, Strategy, Competitive Advantage.